Evaluating the robustness of UK term structure decompositions using linear regression methods - Malik, Sheheryar; Meldrum, Andrew (Journal of Banking & Finance, 2016)
Dynamic no-arbitrage affine term structure models (ATSMs) have become the standard framework for monetary policy-makers to decompose long-term bond yields into expectations of future short-term risk-free interest rates and the term premia that compensate investors in long-term bonds for risk. This paper presents estimates of ATSMs for the UK and explores how much weight users of these models can place on point estimates of term premia. Over much of the period since the early 1990s, broad movements in estimated premia are robust across a wide range of reasonable specifications. But there is substantial model and parameter uncertainty associated with these models and estimates of the time-series dynamics of yields may be biased in short samples. This model uncertainty is greater towards the end of our sample period, when bond yields have been well below historically normal levels.